2017
DOI: 10.1615/intjmedmushrooms.v19.i6.10
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Inhibitory and Immunomodulatory Activities of Wild Mushrooms from North-Central British Columbia (Canada)

Abstract: Wild mushrooms, especially from North America, have not been systematically explored for their medicinal properties. Here we report screening for the growth-inhibitory and immunomodulatory activities of 12 species collected from multiple locations in north-central British Columbia, Canada. Mushrooms were characterized using morphology and DNA sequencing, followed by chemical extraction into 4 fractions using 80% ethanol, 50% methanol, water, and 5% sodium hydroxide. Growth-inhibitory, immunostimulatory, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 0 publications
2
41
0
Order By: Relevance
“…Voucher specimens for these collections were deposited at the University of Northern British Columbia, Canada. The identity of A. flettii was confirmed using previously described genetic protocols [1,2,22]. The DNA sequence of collections CL128 and CL151 were identical and had highest sequence similarity to a collection of A. flettii GenBank JF899544.1 (99.82% identity/100% coverage).…”
Section: Fungal Collection and Identificationmentioning
confidence: 92%
See 2 more Smart Citations
“…Voucher specimens for these collections were deposited at the University of Northern British Columbia, Canada. The identity of A. flettii was confirmed using previously described genetic protocols [1,2,22]. The DNA sequence of collections CL128 and CL151 were identical and had highest sequence similarity to a collection of A. flettii GenBank JF899544.1 (99.82% identity/100% coverage).…”
Section: Fungal Collection and Identificationmentioning
confidence: 92%
“…Albatrellus flettii specimens were sequentially extracted with 80% ethanol, 50% methanol, water and 5% NaOH as previously described [1,2]. Solvents were completely removed by rotovap and powdered extracts were obtained by lyophilization.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the outset of this research, it was hypothesized that wild mushrooms in Northern British Columbia contain compounds with potent bio-activities. The results from this study showed for the first time that indeed Northern BC is home to a large variety of mushrooms containing potent growth inhibitory compounds 97 . The extraction methods developed and adapted (using both the manual and speed extractor) during this study have laid the critical foundation for future mushroom research studies at UNBC and elsewhere.…”
Section: Chapter 4 -General Discussionmentioning
confidence: 65%
“…collected in the forest of British Columbia, whereby the structure of the compound was elucidated with the aid of both onedimensional (1-D) and two-dimensional (2-D) Nuclear Magnetic Resonance (NMR) along with Mass Spectrometry (MS) analysis; however, the bioactivity of the compound isolated was not described (Ming et al 2002). Later, Van et al (2009) (Smith et al, 2017). In addition, a growth-inhibitory polysaccharide (GIPinv) was successfully purified from Paxillus involutus (Batsch) Fr., a forest mushroom also found close to urban trees, which exerted potent growth-inhibitory activity against several cancer cell lines by inducing apoptosis in cancer cells (Barad et al, 2018).…”
Section: Mushrooms and Their Bioactivity Profile In North Americamentioning
confidence: 99%